Influence of sustained rumensin release on steer performance and forage utilization - B. Cochran; E. Vanzant; T. Avery; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1988)
Steers managed within an intensive-early stocking program and receiving Rumensin® via a slow-release bolus tended to have higher average daily gains than steers not receiving Rumensin. However, forage organic matter intake, fill, digestibility, and diet selection showed little response to Rumensin administration.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Rumensin; Steer; Performance; Forage